The effects of a ten-week step aerobic training program on aerobic capacity of college-aged females - Chapek, Constance L. (My University, 1992)
The purpose of this study was to examine the effects of a 10-week step aerobic training program on the maximal oxygen consumption (VO2max) of college-aged women (mean age - 19.4 yrs). Fifty apparently healthy females between the ages of 18 and 25 years participated in the training study. Subjects in the experimental group exercised 3 times per week for 10 weeks. The average heart rate maintained during the training was 150 bpm which represented 76% of HRmax. Twenty-one experimental group Ss and 29 control group Ss performed a maximal treadmill test to volitional exhaustion prior to and upon completion of the study. The variables analyzed included resting HR (bpm), body weight (lbs), rating of perceived exertion (RPE), treadmill run time, absolute VO2max (L/min), relative VO2max (ml/kg/min), VEmax (BTPS) (L/min), RERmax, and HRmax (bpm). The results showed significant (p < .05) between-group differences in mean treadmill run time, absolute VO2max, relative V02max, HRmax, and VEmax. The experimental group had increases in treadmill run time (33.1%), absolute VO2max (11.5%), relative VO2max (11.7%), HRmax (l.O%), and VEmax (6.7%) which were significantly greater than the control group. No significant (p > .05) between-group differences were observed in body weight, RERmax, RPE, and resting HR.
Keywords: Step aerobics - Physiological aspects; Exercise for women - Physiological aspects